العلاقة بين الذكاء التسويقي والاحتفاظ بالعملاء: تحليل الدور الوسيط للوعي بالعلامة التجارية: دراسة تطبيقية على عملاء البنوك التجارية بمحافظة الدقهلية - النجار، عماد عبدالعزيز عيد القصبي (جامعة بورسعيد - كلية التجارة, 2024)
تتناول هذه الدراسة بيان دور الوعي بالعلامة التجارية بوصفه متغيرا وسيطا في العلاقة بين الذكاء التسويقي والاحتفاظ بالعملاء دراسة تطبيقية على عملاء البنوك التجارية بمحافظه الدقهلية. كما تهدف هذه الدراسة إلى دراسة العلاقة بين أبعاد الذكاء التسويقي، وأبعاد الاحتفاظ بالعملاء، وأبعاد الوعي بالعلامة التجارية لدى عملاء البنوك التجارية بمحافظة الدقهلية. وأيضا تحديد التأثير المباشر والغير مباشر لمتغيرات الدراسة. وتوصلت هذه الدراسة إلى وجود علاقة ارتباط معنوية بين أبعاد الذكاء التسويقي، وأبعاد الاحتفاظ بالعملاء، وأبعاد الوعي بالعلامة التجارية لدى عملاء البنوك التجارية بمحافظة الدقهلية. كما يوجد تأثير معنوي مباشر لأبعاد الذكاء التسويقي على أبعاد الوعي بالعلامة، يوجد تأثير معنوي مباشر لأبعاد الذكاء التسويقي على الاحتفاظ بالعملاء، كما يوجد تأثير معنوي مباشر لأبعاد الوعي بالعلامة التجارية على الاحتفاظ بالعملاء لدى عملاء البنوك التجارية بمحافظة الدقهلية، بالإضافة إلى وجود تأثير معنوي إيجابي غير مباشر لأبعاد الذكاء التسويقي على الاحتفاظ بالعملاء من خلال الدور الوسيط لأبعاد الوعي بالعلامة التجارية لدى على عملاء البنوك التجارية بمحافظة الدقهلية. This study provides an explanation of the role of the brand awareness as a mediator in the relationship between marketing intelligence and customers' retention, an applied study on the customer's commercial banks in Dakahlia Governorate. This study also aims to examine the relationship between the dimensions of the marketing intelligence, the dimensions of customer retention, and the dimensions of the brand awareness among commercial bank customers in Dakahlia Governorate. In addition, determine the direct and indirect effect of the study variables. This study found a significant correlation between the dimensions of marketing intelligence, the dimensions of customer retention, and the dimensions of brand awareness among commercial bank customers in Dakahlia Governorate. There is also a direct significant effect of the dimensions of marketing intelligence on the dimensions of brand awareness, there is a direct significant effect of the dimensions of the marketing intelligence on the customer retention, and there is a direct significant effect of the dimensions of brand awareness on the customer retention among bank customers in Dakahlia Governorate. In addition to there is a positive indirect significant effect of the dimensions of the marketing intelligence on customer retention through the mediating of the role of the dimensions of brand awareness among bank customers in Dakahlia Governorate.
Keywords: ريادة الأعمال -- استراتيجيات التسويق -- الخدمات المصرفية -- خدمة العملاء -- العلامة التجارية